CLP1, a Novel Plant Homeo Domain Protein, Participates in Regulating Cellulase Gene Expression in the Filamentous Fungus Trichoderma reesei - Wang, Lei; Yang, Renfei; Cao, Yanli; Zheng, Fanglin; Meng, Xiangfeng; Zhong, Yaohua; Chen, Guanjun; Zhang, Weixin; Liu, Weifeng (Frontiers in Microbiology, 2019)
The stringent regulatory network of cellulase gene expression in the filamentous fungus Trichoderma reesei involves multiple transcriptional regulators. However, identification and mechanistic investigation of these regulators are not finished yet. Here, we identified a novel transcriptional regulator CLP1, a PHD domain protein that participates in regulating T. reesei cellulase gene expression. Phylogenetic analyses demonstrated that CLP1 homologues are widely distributed in the Trichoderma species. We demonstrated that CLP1 is a nuclear protein and lack of CLP1 significantly impaired the induced expression of cellulase genes. ChIP experiments showed CLP1 binding to the cellulase gene promoters specifically under cellulose conditions, and compromised XYR1 occupancy on the same promoters in the absence of CLP1 at the early induction stage. XYR1 overexpression fully rescued the defect in cellulase production but not the defect in conidia formation in the clp1 null mutant. Further analysis revealed that the PHD domain is required for the appropriate CLP1 targeting to the nucleus as well as the induced cellulase gene expression and conidiation. Taken together, these data suggest a specific role of CLP1 in the regulation of cellulase gene expression in T. reesei.